2014
DOI: 10.1002/jcb.24728
|View full text |Cite
|
Sign up to set email alerts
|

CCN2 as a Novel Molecule Supporting Energy Metabolism of Chondrocytes

Abstract: CCN2/connective tissue growth factor (CTGF) is a unique molecule that promotes both chondrocytic differentiation and proliferation through its matricellular interaction with a number of extracellular biomolecules. This apparently contradictory functional property of CCN2 suggests its certain role in basic cellular activities such as energy metabolism, which is required for both proliferation and differentiation. Comparative metabolomic analysis of costal chondrocytes isolated from wild-type and Ccn2-null mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 36 publications
(50 reference statements)
4
35
0
Order By: Relevance
“…Supporting these notions, previous findings conducted in vitro indicate that CCN2 promotes the proliferation, maturation and hypertrophy of growth-plate chondrocytes [1,49]. Recently, it was revealed that CCN2 promotes these apparently opposite cell biological events, i.e., proliferation and differentiation, at least in part by supporting the energy metabolism in chondrocytes [54]. Proliferation, migration, adhesion and tube formation of vascular endothelial cells are also enhanced by CCN2 [4].…”
Section: Skeletal Developmentmentioning
confidence: 70%
“…Supporting these notions, previous findings conducted in vitro indicate that CCN2 promotes the proliferation, maturation and hypertrophy of growth-plate chondrocytes [1,49]. Recently, it was revealed that CCN2 promotes these apparently opposite cell biological events, i.e., proliferation and differentiation, at least in part by supporting the energy metabolism in chondrocytes [54]. Proliferation, migration, adhesion and tube formation of vascular endothelial cells are also enhanced by CCN2 [4].…”
Section: Skeletal Developmentmentioning
confidence: 70%
“…For example, downregulation of glycolysis-related genes such as Pgm1 , Pgam1 , and Eno1 , and decrease in glycolytic activity and ATP levels have been reported in chondrocytes from Ctgf ( Ccn2 )-null mice (Maeda-Uematsu et al, 2014; Murase et al, 2015). It is likely that CTGF regulates expression of glycolysis-related genes after hyperthermia to prevent cancer cells from energy-stressed cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these data, the other high-energy bearing trinucleotides, GTP, UTP, and CTP, were also less abundant in Ccn2-null chondrocytes. As such, a novel function of CCN2 that supports the energy metabolism of chondrocytes was uncovered by a metabolomics approach [65].…”
Section: Novel Properties Of Ccn2 Revealed By Metabolomic Analysismentioning
confidence: 99%
“…However, it should be noted that, even in the absence of CCN2, chondrocytes remain viable, proliferative, and capable of producing cartilaginous ECM molecules, albeit at reduced levels. Thus, CCN2 is not solely required for maintaining the basal activity of chondrocytes, but helps them to be more biologically active [65].…”
Section: The Metabolic Mediator Of Ccn2 Revealed By a Trans-omic Apprmentioning
confidence: 99%